2011
DOI: 10.1177/1074248411427402
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban and Rivaroxaban Safety After Hip and Knee Arthroplasty

Abstract: Direct experimental safety comparisons of Xa coagulation factor direct inhibitors, apixaban and rivaroxaban, on their approved therapeutic indications have not been identified. Due to recently raised safety concerns, a meta-analysis was carried out pooling data from studies identified on a Medline and Cochrane Library search in order to better evaluate the safety profile of both drugs. Abstracts from scientific meetings were also searched from 2003 to 2011. Primary and secondary outcome measures were major ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Rivaroxaban is a highly selective, oral direct factor X a inhibitor that can competitively inhibit the freedom and binding of factor X a as well as prothrombin activity [12]. Rivaroxaban reaches a peak 2 h after oral administration with a half-life of 4-6 h and is characterized by a wide therapeutic window, high bioavailability, good pharmacokinetic stability and predictable efficacy [13,14]. Our results indicate that there were 14 patients in the LMWH group with both symptomatic and asymptomatic DVT, but only three patients in the rivaroxaban group with asymptomatic DVT; the patients' postoperative femoral superficial vein and popliteal vein diameters stenosis in the rivaroxaban group are much lighter than the LMWH group, similar to those described above.…”
Section: Discussionmentioning
confidence: 99%
“…Rivaroxaban is a highly selective, oral direct factor X a inhibitor that can competitively inhibit the freedom and binding of factor X a as well as prothrombin activity [12]. Rivaroxaban reaches a peak 2 h after oral administration with a half-life of 4-6 h and is characterized by a wide therapeutic window, high bioavailability, good pharmacokinetic stability and predictable efficacy [13,14]. Our results indicate that there were 14 patients in the LMWH group with both symptomatic and asymptomatic DVT, but only three patients in the rivaroxaban group with asymptomatic DVT; the patients' postoperative femoral superficial vein and popliteal vein diameters stenosis in the rivaroxaban group are much lighter than the LMWH group, similar to those described above.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of different regimens of comparators complicates an integrated assessment of the overall efficacy and safety of new agents relative to the current standard of care, as well as indirect comparisons among the new agents, but this factor has not always been considered in published meta‐analyses for single1, 2, 3, 4, 5, 6, 7 or multiple8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 agents. Dose regimen of the comparator has been acknowledged as a potential source of heterogeneity for a number of previous analyses 1, 2, 3, 5, 6, 10, 11, 12, 13, 14, 18.…”
mentioning
confidence: 99%
“…They found that in THA patients, rivaroxaban 10mg daily compared to dabigatran 150 or 220 mg daily was more effective in preventing VTE (RR 0.46) but caused more bleeding (RR = 1.14) [79] . In a similar indirect comparison, Alves et al [80] reported no differences between rivaroxaban and apixaban for total or major bleeding safety in the subgroup of patients undergoing THA.…”
Section: Comparison Of Tsoas In Thamentioning
confidence: 95%
“…However, several investigators have published systematic analyses that attempt to give perspective regarding the comparable efficacy and/or bleeding risk of individual new agents [77][78][79][80] . At least two meta-analyses have provided results that indirectly compared the efficacy and safety of the TSOAs, while one other meta-analysis focused solely on the safety [77][78][79][80][81] . Dabigatran, rivaroxaban, and apixaban were indirectly compared by Gómez-Outes et al [78] based on study results that compared the given TSOA to enoxaparin.…”
Section: Comparison Of Tsoas In Thamentioning
confidence: 99%